High-efficiency perovskite solar cells based on MAI(PbI2)1−x(FeCl2)x absorber layers. (1st January 2018) - Cai, Qingbin; Li, Haitao; Jiang, Yaxiao; Tu, Limin; Ma, Li; Wu, Xiaojie; Yang, Shi-e; Shi, Zhifeng; Zang, Jinhao; Chen, Yongsheng
Graphical abstract: Highlights: Efficient metal halide substituted MAI(PbI2 )1−x (FeCl2 )x perovskite solar cells. A power conversion efficiency above 17% is achieved for the device with FeCl2 substituting of 1.8%. FeCl2 substitution of PbI2 for highly reproducible large crystals. Cl – ions play an important role in suppressing the traps in the band gap to decrease the nonradiative recombination. Abstract: In this paper, we present a successful partial substitution of PbI2 by a much less expensive and toxic FeCl2 in perovskite films, namely MAI(PbI2 )1−x (FeCl2 )x (MA = CH3 NH3 + ), and the followed effects on the performance of planar heterojunction perovskite solar cells (PSCs). The incorporation of a small content of Fe and Cl ions into the perovskite films could improve the growth morphology, enhance the crystallinity, increase the carrier lifetimes, as well as tune the material work function and Fermi level without significantly changing the band gap. Consequently, by adjusting the FeCl2 substitution fraction into the perovskite films, a power conversion efficiency above 17% is achieved with a high open-circuit voltage up to 1.10 V. Our work implies that conventional chlorides as substituting material of PbI2 have huge potential for the fabrication of more ecological PSCs.